Empowering solar innovations at Pamantasan ng Lungsod ng Maynila: sun tracking hydrophobic coating panels for self-cleaning with actuator DC motors and hybrid charging. - Karl Nino B. Dela Rosa, Kean Elley Red B. Llamado, Rica P. Quines, Jowen V. Sibucao. 4 0 16; 5
ABSTRACT: This research explores the integration of advanced solar technologies to optimize energy generation and usage at Pamantasan ng Lungsod ng Maynila (PLM). Focusing on sun-tracking panels driven by actuator DC motors, the study aims to enhance solar panel efficiency by dynamically adjusting their orientation towards the sun. Additionally, self-cleaning mechanisms, specifically solenoid valves, are investigated to mitigate performance degration caused by environmental factors, ensuring consistent energy output. This study aims to address reducing carbon emissions and increasing our reliance on renewable energy sources. Employing a combination of approaches in this investigation, the researchers sought to find sustainable solutions. This study has facilitated the development of eco-friendly alternatives, highlighting its significance not just for individuals and students but also for the environment. The researchers recognized the potential of harnerssing solar energy through arrays on university campuses, contributing to the expansion of renewable energy resources and subsequently decreasing electricity consumption. Furthermore, the incorporation of built-in device charging capabilities enhances the practicality and accessibility of solar energy for PLM's community. Through this interdisciplinary approach, the research seeks to empower PLM with resilient and efficient solar solutions, contributing to the institution's commitment to sustainability and renewable energy adoption.
Undergraduate Thesis: (Bachelor of Science in Computer Science) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2